(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The role of Micro, Small, and Medium Enterprise was very important for country’s economic development. Micro, Small, and Medium Enterprise contributed Indonesia Gross Domestic Product approximately 30% and became a solution eradicate poverty. Decreasing phenomena of Micro, Small, and Medium Enterprise data element percentage from 2019 until 2020 indicated that there was not ever significant increasing about green economy implementation on Micro, Small, and Medium Enterprise. Micro, Small, and Medium Enterprise empowerment which adopted green economy principal became highlight in sustainable economic development. Green economy implementation for Micro, Small, and Medium Enterprise such as product packaging, raw material usage, and technology. Problem statement in this research is stated by problem questions: (1) How is the impact of product packaging, raw material usage, and technology simultaneously toward sustainability Micro, Small, and Medium Enterprise in Semarang city? (2) How is the impact of product packaging partially toward sustainability Micro, Small, and Medium Enterprise in Semarang city? (3) How is the impact of raw material usage partially toward sustainability Micro, Small, and Medium Enterprise in Semarang city? (4) How is the impact of technology partially toward sustainability Micro, Small, and Medium Enterprise in Semarang city? Research purposes: (1) Knowing the impact of product packaging, raw material usage, and technology simultaneously toward sustainability Micro, Small, and Medium Enterprise in Semarang city. (2) Knowing the impact of product packaging partially toward sustainability Micro, Small, and Medium Enterprise in Semarang city. (3) Knowing the impact of raw material usage partially toward sustainability Micro, Small, and Medium Enterprise in Semarang city. (4) Knowing the impact of technology partially toward sustainability Micro, Small, and Medium Enterprise in Semarang city. This research is belong to quantitative research and using kind of Likert Scale. Researcher uses primary data. Research population are all of Micro, Small, and Medium Enterprise in Semarang city. Sample which is taken are 70 Micro, Small, and Medium Enterprise in Semarang city